A redescription of Culicoides griseidorsum Kieffer, 1918, with comments on subgeneric position of some European taxa (Diptera: Ceratopogonidae) - Szadziewski, Ryszard; Filatov, Serhii; Dominiak, Patrycja (Zootaxa, 2016)
Culicoides griseidorsum Kieffer, 1918 is formally redescribed, and the male described and illustrated for the first time. The species is placed within Sensiculicoides Shevchenko, 1977 the subgenus restored from the synonymy with Oecacta Poey, 1853. A checklist of European species placed in subgenera Sensiculicoides and Oecacta is provided.